A concise field guide to post-communist regimes : actors, institutions, and dynamics - Magyar, Bálint, 1952-; Madlovics, Bálint, 1993- (Central European University Press, 2022)
"While the literature of hybrid regimes has given up the presumption that post-communist countries must democratize, its language and concepts still mostly relate to Western democracies. Magyar and Madlovics strongly argue for a vocabulary and grammar tailored to the specifics of the region. In 120 theses they unfold a conceptual framework with (1) a typology of post-communist regimes and (2) a detailed presentation of ideal-type actors and the political, economic, and social phenomena in these regimes. The book is a more digestible companion to the 800-page The Anatomy of Post-Communist Regimes (CEU Press, 2020), which was a detailed theoretical study with plenty of empirical illustrations. Each of the 120 theses contains a statement and its concise discussion supported by illustrative tables, figures, and QR-codes that connect the interested reader to the more detailed analysis in the Anatomy. In a condensed variety, this book has kept the holistic approach of the Anatomy and treats the spheres of political, market, and communal action as parts of a single, coherent whole. The endeavor to synthesize a vast range of ideas does not, however, result in a too complicated text. On the contrary, freed from the implicit presumptions of democracy theory, the new terminology yields a readily usable toolkit of unambiguous means of expression to speak about post-communism"--